Human Capacity Development as a Tool to Maximize the 2045 Demographic Bonus and Strengthen National Defense in Indonesia - Henry Iheanacho Eze; Hikmat Zakky Almubaraq; Anak Agung Bayu Perwita; Reinpal Falefi (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
Human capacity building offers an opportunity for Indonesia’s demography bonus and enhancement of national defense. This lofty goal necessitates this study to assess how human capacity development could be leveraged as a tool for the demographic bonus towards enhancing national defense. The study utilizes qualitative methodology in addressing the research objectives. To maximize a projected demographic bonus by 2045 for Indonesia, a key strategy for state defense is the maximization of human resources to ensure productivity. Three efforts to this effect have been identified and studied. The Merdeka Belajar (Independent Learning) curriculum and the Merdeka Kampus (Independent Campuses) initiative identified processes for educational reform in Indonesia to face the challenges of the demographic bonus in 2045. Another tangible means for human capacity development is the implementation of the Pancasila Student Profile Project, which actualizes the values of Pancasila in the educational process and everyday life through student activities. The creation of excellent and competent human resources is not only to support the economic aspects and industry needs but also in the interests of national defense. The study concluded through holistic education, strengthened defense consciousness, industry-academia collaborations, and a persistent drive for leadership and values, Indonesia is not just preparing for a demographic bonus but